2016
DOI: 10.1002/acr.22815
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Risk of Harm Associated With the Use of Targeted Immunomodulators: A Systematic Review

Abstract: ObjectiveTo systematically compare the risk of adverse events (AEs) for 13 targeted immunomodulators (TIMs) indicated for ankylosing spondylitis (AS), inflammatory bowel diseases, juvenile idiopathic arthritis, plaque psoriasis, psoriatic arthritis (PsA), or rheumatoid arthritis (RA).MethodsWe searched electronic databases through July 2015 to retrieve randomized controlled trials (RCTs) and observational studies comparing AEs between 2 or more TIMs head‐to‐head. We reported on the following outcomes: number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 48 publications
1
11
0
1
Order By: Relevance
“…These observations are confirmed by other Greek studies [11, 18, 19]. In line with our results, a recent systematic review highlighted that the risk of treatment discontinuation due to adverse events was greater for infliximab than for adalimumab or etanercept in RA patients [22]. The same review revealed a greater risk for serious infections with infliximab than with the other two therapeutic choices, while we showed that rates of serious infections did not differ statistically among the three drugs.…”
Section: Discussionsupporting
confidence: 93%
“…These observations are confirmed by other Greek studies [11, 18, 19]. In line with our results, a recent systematic review highlighted that the risk of treatment discontinuation due to adverse events was greater for infliximab than for adalimumab or etanercept in RA patients [22]. The same review revealed a greater risk for serious infections with infliximab than with the other two therapeutic choices, while we showed that rates of serious infections did not differ statistically among the three drugs.…”
Section: Discussionsupporting
confidence: 93%
“…Increased rates of SIEs are an acknowledged risk of medications that have an immunomodulatory effect, including tofacitinib and bDMARDs [31,34,35]. The IRs for SIEs in the tofacitinib dose-comparison cohort (1.3 and 2.0 for patients with PsA receiving tofacitinib 5 and 10 mg BID, respectively) and in the all-tofacitinib comparison cohort (1.4) were consistent with the IR of 2.7 reported for tofacitinib in patients with RA who participated in phase I, II, III, and LTE studies [31] and 1.9 in patients with psoriasis in phase III and LTE studies [32].…”
Section: Discussionmentioning
confidence: 99%
“…In rheumatoid arthritis (RA) and inflammatory bowel disease (IBD), data regarding the association of HZ and treatment with tumor necrosis factor (TNF) inhibitors are contradictory (6). Recent observational studies reported that treatment with TNF inhibitors is associated with increased risk for HZ (7)(8)(9)(10)(11)(12) and more severe HZ disease (13,14).…”
Section: Introductionmentioning
confidence: 99%